Ironwood - Connelly, Michael, 1956- (Connelly, Michael, 1956- Catalina novel., 2026)
"Sworn to protect a scenic island meant to be far from the evils of the mainland, Detective Sergeant Stilwell can feel danger closing in. Detective Sergeant Stilwell knows that his posting on Catalina Island is no paradise, but to most residents, it seems blissfully separated: by twenty-two miles of ocean: from the troubles of Los Angeles County. But now a threat is coming to his safe haven. Acting on a tip from a confidential informant, Stilwell and his deputies watch a plane land in the middle of the night at the Airport in the Sky, a remote airstrip in the mountains. A duffel bag of drugs is dropped and the deputies move in, but things quickly go sideways. While Stilwell chases the fleeing pickup man into the mountainside brush, shots are fired on the runway and the plane flies off. An internal inquiry follows, putting Stilwell on the bench until he is cleared of responsibility for the disastrous operation. But he is determined to find out who brought deadly violence to his island, and begins his own secret investigation into the drug deal gone wrong. While under orders to remain in the sheriff's substation, he finds in the lost and found a valuable backpack that was never claimed. He traces it to a woman who disappeared while hiking on the island four years ago. But then why was the pack only turned in two months back? Now thoroughly intrigued, he follows the mystery all the way to the LAPD's Open-Unsolved Unit and Detective Renee Ballard. Stilwell and Ballard work the case from both sides of the channel, and soon realize they are on the trail of a criminal who revels in taunting the authorities. Meanwhile, frustrated at being shut out of an investigation on his own island, Stilwell risks his already shaky standing in the department to pursue a case whose reach is wider than he ever imagined."--